Was Hypervascular Hepatocellular Carcinoma Visible on Previous Gadoxetic Acid-Enhanced Magnetic Resonance Images? - Ichikawa, Shintaro (Liver Cancer, 2015)
BACKGROUND: During the follow-up of patients with chronic liver disease, hypervascular hepatocellular carcinomas (HCCs) can develop either from pre-existing high-risk nodules or by de novo hepatocarcinogenesis. The purpose of this study was to evaluate, by retrospective analysis, the detectability and signal intensity on previous hepatocyte-phase gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (EOB-MRI) of hypervascular HCC initially detected on current EOB-MRIs. METHODS: We examined 50 initially detected hypervascular HCCs that showed typical enhancement features on EOB-MRI in 39 patients whose previous EOB-MRI images obtained 6-19 months earlier were available. The detectability of each hypervascular HCC on the hepatocyte phase images of previous EOB-MRIs was assessed. The imaging features on hepatocyte-phase images of previous EOB-MRIs at the locations where hypervascular HCCs were found on the current EOB-MRI images were classified as detectable or undetectable. The signal intensities of detectable nodules (defined as group A) on hepatocyte-phase images of previous EOB-MRIs were classified as hypo-, iso-, or hyperintensity. Nodules undetectable on the hepatocyte-phase images of previous EOB-MRIs were assigned to group B. RESULTS: Twenty-two (22/50, 44%) hypervascular HCCs were detectable on the earlier hepatocyte phase images (group A). In contrast, 28 (28/50, 56%) hypervascular HCCs were not detectable on the hepatocyte phase of earlier EOB-MRI images (group B). CONCLUSION: When the previous EOB-MRI images were used as the reference, more than half (28/50, 56%) of hypervascular HCCs initially appearing on the current EOB-MRI images were found not to have developed from nodules detectable on the previous MRIs through the traditionally accepted process of multistep carcinogenesis. Instead, they seemed to have developed via an “imaging-occult” process of carcinogenesis in patients with chronic liver diseases.